Short explanation of humpback grouper - Indra Surya Winata (PT. Gyandharma Global Media, 2025)
Grouper fish are widely distributed in coastal waters, both in tropical and subtropical regions, and are a type of fish that lives in coral habitats, so they are often referred to as reef fish. In Indonesia, there are various types of grouper fish, one of which is the humpback grouper (Cromileptes altivelis), which is popular because of its high economic and ecological value. This article briefly explains about humpback grouper, both in terms of morphology, habitat, reproduction and spawning.